Karakteristik Tegangan Tembus AC Pada Material Isolasi Padat Campuran Epoxy Resin Dengan Cangkang Kelapa Sawit - Yan Habibillah Pesa; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Abstract—Epoxy resins are the solid insulation that are widely used to increase the high voltage insulators. In order to increase the dielectric and mechanical strength of epoxy resins can be mixed by using materials such as alumina, palm kernel shells and cnt (carbon nano tubes). From this research of epoxy resin mixed with palm kernel shells with a diameter of 1 mm looks the electrical breakdown characteristics uniquely. With the addition of palm kernel shells can raise breakdown voltage of epoxy resin, compared to pure epoxy resin. The increasing of breakdown voltage is affected by the dielectric strength of palm kernel shells were higher rather than epoxy resin. Discharge currents were recorded from the measurements at laboratory on samples showed different results. At the time of the solidinsulator is approached the electrical breakdown, discharge currents can have a lot of pulses. From these results, a mixture of epoxy resin and palm kernel shells can be used as a new insulator. The properties ofdielectric strength and discharge currents that occur at the time of measurement in the lab shows the different and unique.Keywords ; epoxy resin, palm kernel shell, breakdown voltage, discharge current